Tradition in the Frame : Photography, Power, and Imagination in Sfakia, Crete - Kalantzis, Konstantinos (Book collections on Project MUSE., 2019)
"Sfakians on the island of Crete are known for their distinctive dress and appearance, fierce ruggedness, and devotion to traditional ways. The author explores how Sfakians live with the burdens and pleasures of maintaining these expectations of exoticism for themselves, for their fellow Greeks, and for tourists"--